Ethyl acetate extracts of Nepenthes ventricosa x sibuyanensis leaves cause growth inhibition against oral cancer cells via oxidative stress - Tang, Jen-Yang (Onco Targets Ther, 2019)
Introduction: The genus Nepenthes of the pitcher plants contains several natural and hybrid species that are commonly used in herbal medicine in several countries, but its possible use in cancer applications remains unknown as yet. Methods: In this study, we investigated the antioral cancer properties using ethyl acetate extracts of the Nepenthes hybrid (Nepenthes ventricosa x sibuyanensis), namely EANS. The bioactivity was detected by a MTS-based cell proliferation assay and flow cytometric or Western blot analysis for apoptosis, oxidative stress, and DNA damage. Results: Treatment for 24 hrs of EANS inhibited all three types of oral cancer cells that were tested (Ca9-22, CAL 27, and SCC9), with just a small difference to normal oral cells (HGF-1). This antiproliferation was inhibited by pretreatments with the reactive oxygen species (ROS) scavenger N-acetylcysteine (NAC), and the apoptosis inhibitor (Z-VAD). EANS treatment increased the subG1 population and it also dose- and time-dependently induced annexin V- and pancaspase-detected apoptosis as well as cleaved caspases 3 and 9 overexpressions in the oral cancer cells (Ca9-22). After EANS treatment of Ca9-22 cells, intracellular ROS and mitochondrial superoxide (MitoSOX) were overexpressed and mitochondrial membrane potential (MMP) was disrupted. Moreover, DNA damages such as γH2AX and 8-oxo-2ʹ-deoxyguanosine (8-oxodG) were increased after EANS treatment to Ca9-22 cells. The EANS-induced effects (namely, oxidative stress, apoptosis, and DNA damage) were suppressed by ROS scavenger. Conclusion: Our findings demonstrated that EANS inhibits ROS-mediated proliferation against oral cancer cells.